Some of my Best Friends are Romanticists: Shelley and the Queer Project in Romanticism - Berry, Amanda (Romanticism on the Net)

(untitled) (Université de Montréal, 2004)
Abstract“Was Percy Bysshe Shelley Gay?” This essay first explores the quality and effects of the question, recently posed both in an internet gay magazine, Gay Today, and to the academic discussion list associated with the North American Society for the Study of Romanticism, NASSR-L. The power of this question to interrupt discussion among critics in the field, despite ongoing work in queer Romanticism, suggests that identity politics still shapes many of the necessary debates in both Romanticism and critical sexuality studies. The essay further generates a model of queer analysis as it traces Shelley’s conversion of the historical Count Cenci’s acts of sodomy into what Shelley regards as “a very poetical circumstance,” incest. Shelley imagines a complex alibi with which he shapes his own intense curiosity about intimacy between men into a set of effects found in his writing during his earliest time in Italy, while he was translating Plato’s Symposium (“for Mary”), composing a supplemental essay on Greek Love, and writing The Cenci.